Culturable bacterial phylogeny from a shallow water hydrothermal vent of espalamaca (Faial, Azores) reveals a variety of novel taxa - Rajasabapathy, Raju; Mohandass, Chellandi; Colaco, Ana; Dastager, Syed Gulam; Santos, Ricardo Serrao; Meena, Ram Murti (Current Science, 2014)
Phylogenetic diversity of the 16S rRNA gene associated with the domain bacteria was examined at the level of operational taxonomic units (OTUs) using the rarefaction analysis from a newly identified shallow water hydrothermal vent, Espalamaca in the Azorean Island Faial (Horta), North Atlantic Ocean. Diluted sea water nutrient agar amended with metals manganese, lead, iron and element sulphur, could help in retrieving highest OTUs (95) from the vent and 39 OTUs from nonvent. Molecular tools implemented on bacterial census indicated the occupancy of gamma-Proteobacteria by 55.78%, alpha-Proteobacteria by 21.05% and 12.63% of Bacteroidetes in the total population. Occurrence of novel species maximized with alpha-Proteobacteria (11/20) followed by Bacteroidetes (5/12) signified the necessity of studying these groups to strengthen the biodiversity database. Shannon index (H') and the Chao I richness estimator illustrated a strong bacterial community in the venting area. The current study confers many bacterial genera which were not reported earlier in any of the shallow water vents and adds 33 new taxa to the database.
Keywords: Bacterial phylogeny; metals; novel taxa; rarefaction analysis; shallow vent